Karakteristik Cookies Ampas Kelapa (Cocos nucifera L) Dan Tepung Kepala Udang Vanname (Litopenaeus vannamei) - Husain, Rahim; Djano, Fazran; Harmain, Rita Marsuci (Jambura Fish Processing Journal, 2025)
Cookies are one of the crunchy, thin, flat and small-sized pastries. The purpose was to formulate coockies using coconut pulp (Cocos nucifera L) and vanname shrimp head flour (Litopenaeus vannamei), conduct organoleptic tests and proximate levels (water content, ash content, protein content, fat and carbohydrate content). The formulation is coconut pulp and vanname shrimp head flour with treatment P0 (without the use of coconut pulp and shrimp head flour), P1 (15 g coconut pulp: 5 g shrimp head flour), P2 (20 g coconut pulp: 10 g shrimp head flour) and P3 (25 g coconut pulp: 15 g shrimp head flour). The experimental design used a single factor Completely Randomised Design. Organoleptic data analysis using Kruskal-wallis, if significant using Duncan's further test. Analysis of variance (ANOVA) for proximate testing of coconut pulp coockies and vanname shrimp head flour. Based on the results of hedonic organoleptic test, coconut pulp cookies and vanname shrimp head flour were selected in formula P2 with the criteria of liking on the parameters of texture value 4.28, aroma 4.2, taste 4.6 and colour 4.16. The results of proximate testing of the selected formula P2 with a moisture content value of 5.84 - 4.63% are close to SNI standard number 01-2973-2011 regarding biscuit quality requirements, Ash content value of 2.63 - 3%, protein content of 6.58 - 11.08% exceeds the SNI standard (01-2973-2011), fat  and carbohydrate content value of 73.47 - 78.18% meets the SNI standard (01-2973-2011).